Laboratory Investigation on Enhancing Stiffness Performance of Garnet Modified Hot Mix Asphalt - Cathrina Ambros,; Mohamad Taher, Mohammad Nasir; Hazirah Bujang, (Recent Trends in Civil Engineering and Built Environment, 2025)
Due to many high stress on the pavement, the asphalt road is exposed to numerous strains, which results in numerous defects and cracks. Road users face numerous issues as a result of these flaws, including discomfort and decreased safety. All types of pavement require regular maintenance due to several factors such as temperature changes, overload, and the impact of precipitation from the weather. This paper presents a pavement stiffness assessment incorporating garnet in hot mixture asphalt. Garnet is a group of complex silicate minerals with similar crystalline structures and diverse chemical compositions, and its properties such as angular fractures and relatively high hardness, specific gravity and resistance to degradation make it desirable for many industrial applications. In order to evaluate the performance of garnet as replacement of fine aggregate in Hot-Mix Asphalt, the Marshall mix design AC-14 was employed with proportions of garnet used 0%, 5%,15% and 25%. A total of 60 samples were investigate through Marshall stability and flow test. It is anticipated that the replacement of fine particles in hot-mix asphalt mixtures with garnet increased the stiffness of the pavements, and the increased traffic volume, loading, and variable weather conditions may be managed by the better-quality asphalt pavements.